The Communist Party and Celebrations of the Victory Day (9 May) in Yugoslavia 1945–1955 - Bondžić, Dragomir (Pamięć i Sprawiedliwość, 2019)
T he article deals with meaning of celebrations of 9 May – Victory Day – in Yugoslavia in the first few years after World War II and with the role of the Communist Party of Yugoslavia in organising these ceremonies. It is shown that this holiday was one of the cornerstones of the Communist regime propaganda and a very important occasion for creating the tradition of national liberation struggle and anti-fascism. The main role of Victory Day was to recall the victory over fascism, but also to contribute to consoli-dation of Communists’ rule and to display foreign and inner policy of the new autho-rities in Yugoslavia. The ruling party used the entire content of the celebrations to cre -ate and impose its own image of World War II and the national liberation struggle in Yugoslavia and to present the desirable image of the current international and internal political situation. These celebrations were conceived and designed by the top officers of the Communist Party, in its Agitprop apparatus, and all activities and details were dictated by Party guidelines and directives.